Maximizing the benefits of ERP Systems - Menezes, Paulo André da Conceição (2010)
The ERP (Enterprise Resource Planning) systems have been consolidated in companies with different sizes and sectors, allowing their real benefits to be definitively evaluated. In this study, several interactions have been studied in different phases, such as the strategic priorities and strategic planning defined as ERP Strategy; business processes review and the ERP selection in the pre-implementation phase, the project management and ERP adaptation in the implementation phase, as well as the ERP revision and integration efforts in the post-implementation phase. Through rigorous use of case study methodology, this research led to developing and to testing a framework for maximizing the benefits of the ERP systems, and seeks to contribute for the generation of ERP initiatives to optimize their performance.